Análise das estratégias nutricionais, composição corporal e nível de hidratação de fisiculturistas na Peak Week - REINALDO, Thiago Sousa (2020)
Objective: To describe the nutritional manipulations most used by bodybuilders in the peak week. Materials and Methods: The sample was selected for convenience, consisting of 11 male bodybuilders, three athletes in the Bodybuilding category (senior / master), three classic bodybuilders, one Classic Physique, two Men's Physique and two Muscular Men's Physique, registered officially at the IFBB and who were in preparation for at least 1 year for the championship. Being evaluated in three evaluation periods: baseline (B), weighing (P) and competition (C). Then the nutritional recall, body composition analysis, through perimetry and adipometry, and the specific gravity of the urine were performed. For statistical analysis, an Anova was performed for repeated measures with post hoc Bonferroni, in order to verify the differences over time. In addition, sphericity was checked according to the Mauchly W test and Greenhouse-Geisser correction when necessary. The effect size for each ANOVA was calculated using partial eta squared (η2p), considering 0.01, 0.06 and 0.14 as small, moderate and large, respectively. Results: The ANOVA of repeated measures identified differences over time in body mass [F (1,266; 12,656) = 13.409; p = 0.002; η2p = 0.573], significant post hoc between moment B and P (p <0.001). With regard to body composition, the percentage of fat [F (2; 20) = 4.407; p = 0.026; η2p = 0.306], there was no statistically significant difference. The specific gravity of the urine showed a difference over time [F (2; 20) = 25.885; p <0.001; η2p = 0.721], with a significant difference between the moments between P and C (p = 0.001) and between B and C (p <0.001). Total energy intake [F (2; 20) = 8,924; p = 0.002; η2p = 0.472] and relative [F (2; 20) = 8.837; p = 0.002; η2p = 0.469] presented, respectively, significance in the Anova test. When comparing the moments, the post hoc identified a difference between B and P (p = 0.014) and P and C (p = 0.014) in the variable kcal / total / day. Conclusion: The nutritional strategies most used by bodybuilders in Pkw were the reduction of energy and macronutrient intake up to the time of weighing, and an acute increase in energy and macronutrient intake after weighing, however, no changes in body composition were observed. throughout the moments, in addition to the athletes starting the Pkw in euhydrated state and evolving to a state of severe dehydration on the day of the competition.